First derivative can be found using the quotient rule.

`f'(x) = ((x-1)*1 - x*x)/(x-1)^2`

`f'(x) = (-x^2+x-1)/(x-1)^2`

At critical points, f'(x) = 0

-x^2+x-1=0

Roots can be found by the using the standard equation for quadratic roots.

`x = (-1+-sqrt(1^2-4*(-1)*(-1)))/(2*(-1))`

`x = (-1+-sqrt(-7))/-2`

There are no real roots, therefore, f(x)...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

First derivative can be found using the quotient rule.

`f'(x) = ((x-1)*1 - x*x)/(x-1)^2`

`f'(x) = (-x^2+x-1)/(x-1)^2`

At critical points, f'(x) = 0

-x^2+x-1=0

Roots can be found by the using the standard equation for quadratic roots.

`x = (-1+-sqrt(1^2-4*(-1)*(-1)))/(2*(-1))`

`x = (-1+-sqrt(-7))/-2`

There are no real roots, therefore, f(x) doesn't have any critical points.